Adverse drug reaction profile in Amravati region of India: A pharmacovigilance study - Kishor A Bansod; Mohammed Shakeel Mohammed Bashir; Shilpa S Ingle (Wolters Kluwer Medknow Publications, 2020)
Background: This pharmacovigilance study was conducted in Amravati region of central India to identify the nature and prevalence of adverse drug reactions, which will be helpful for better drug prescription practice and management of diseases. Materials and Methods: Adverse drug reaction reporting forms from April 2016 to March 2019, were collected from the pharmacovigilance center, which include details of demographics, investigations, concomitant drug history, and details of present complaints including reaction details, onset, recovery, drug information, hospitalization, management, and assessment. Results: A total of 19 cases were reported. Approximately 47.4% male and 52.6% female experienced the reactions with age-group ranging from 15 to 75 years. The most common adverse drug reactions were caused by antimicrobial agents (47.6%) followed by other group of drugs (37%) and nonsteroidal anti-inflammatory drugs (15.9%). Polypharmacy was the most common cause (31.6%) with the most common route being intravenous (42.1%). Skin reactions were the most common (84.2%). Antitubercular drugs were more commonly responsible for exfoliative lesions, whereas paracetamol and unknown drugs were responsible for multiple ulcerative lesions. Reactions to antitubercular drugs were considered as possible (15.8%), whereas with other drugs (63.2%), it was probable. Conclusion: It is a tip of the iceberg, which provides important demographic details in which adverse drug reactions were reported. Cutaneous reactions due to common drugs are responsible for hospitalization of the patients. There is an urgent need of training for health-care providers so that reporting can be improved and better picture can emerge.